ABUNDANCE OF PHYTOPLANKTON AS A DETERMINANT OF WATER QUALITY IN THE COASTAL AREA OF DUMAI BARAT DISTRICT, DUMAI CITY, RIAU PROVINCE - Silfia Nurjijar; Tengku Dahril; Yudho Harjoyudanto (Indonesian Journal of Multidisciplinary Science, 2022)
The coastal area in Dumai Barat District has experienced many changes in the function of coastal land and mangroves so that various human activities provide input of organic and inorganic materials that will affect air quality and phytoplankton. This research was conducted in March-April 2022. There are 3 stations with sampling 3 times, once/week. The air quality parameters measured were temperature, brightness, current velocity, dissolved oxygen, free carbon dioxide, pH, salinity, phosphate, nitrate, and phytoplankton. The results show that the temperature is 29.33-32.00oC, brightness is 58.67-69.67 cm, current velocity is 0.99-1.00 m/s, dissolved oxygen is 6.20-8.32 mg/L, free carbon dioxide is 7.92-15.84 mg/L, pH is 7.07-7.10, salinity is 20-28 ppt, phosphate is 0.7661-0.9955 mg/L, and nitrate is 0.6530 -0.8224 mg/L. There were 25 types of phytoplankton found, namely Bacillariophyceae (12 species), Chlorophyceae (6 species), Dinophyceae (1 species), Cyanophyceae (2 species), Euglenoidea (1 species), Coscinodiscophyceae (1 species), and Trebouxiophyceae (2 species ). The abundance of phytoplankton in the coastal area of West Dumai is 15,308-31,603 cells/L. Data analysis shows that the air quality is still good and can be tolerated by phytoplankton organisms with mesotrophic fertility.